Implementasi Program Isbat Nikah di Kelurahan Bulak Banteng Kota Surabaya - Rachmalia Novita Cahyani; Moh. Musleh (Journal of Contemporary Public Administration, 2024)
Isbat nikah is a periodic conjugal marriage program that has been implemented in accordance with the provisions. The program is a means of administrative fulfillment that was previously unrecorded. The purpose of this study is to find out: 1) The role of stakeholders in efforts to encourage the submission of marriage isbat to the community in Bulak Banteng Village. 2) Procedures for administrative recording through the isbat nikah program. Researchers use qualitative approach methods with descriptive research types. The data collection techniques chosen in this study were observation and interviews. Van Metter and Van Horn's implementation theory uses 6 indicators. The results showed that the implementation of the isbat nikah program has run optimally. However, in its implementation, there are obstacles, namely in the aspect of resources that have not been optimally implemented, there are 2 residents who have been registered but canceled to take part in the isbat nikah program due to communication constraints.